Superior vena cava syndrome in lung cancer. (December 2012) - Feng, Yan; Pennell, Nathan A
Summary  Superior vena cava syndrome (SVCS) consists of various symptoms and signs due to intrinsic obstruction or extrinsic compression of the superior vena cava. The most common etiology is thoracic malignancy, with lung cancer being the leading cause (80%). It usually presents with edema of the head, neck and arms, often associated with cyanosis, plethora and distended subcutaneous vessels. The diagnosis is commonly made from physical examination and confirmed by imaging, such as CT scan. SVCS is usually not a medical emergency, but can, in rare cases, cause cardiac or airway compromise, or cerebral edema, which may require urgent interventions such as thrombectomy or endovascular stenting. In lung cancer-related SVCS, radiation and/or chemotherapy are the main treatment options, and tissue diagnosis should be obtained before the initiation of definitive treatment if SVCS is the initial presentation. Randomized controlled trials are still lacking for optimal management of SVCS.